Perspective of Public Interest and Protection of Sustainable Food Land in Java Integrated Industrial and Ports Estate Indonesia - Suyanto; Siti Hafsyah Idris (Dinasti Research, 2025)
Industrial growth and rural development promote balanced development to protect the public interest. Governmental oversight ensures regulation and governance for sustainable industrial growth. The research aims to clarify the modifications in agricultural land use within the Gresik Special Economic Zone or Java Integrated Industrial and Port Estate (JIIPE) from the viewpoint of public interest and land conservation in adherence to Law Number 41 of 2009 on the Protection of Sustainable Food Agricultural Land. The legal norms studied in this research are changes in the function of agricultural land into industrial land from the perspective of public interest, the Farmland Preservation Act, and the Welfare State. Changes in the conversion of agricultural land in Manyar District, Gresik Regency, East Java Province for industrial purposes in the Java Integrated Industrial and Port Estate (JIIPE) Area which was formed based on PP No. 71 of 2021. The Law on the Protection of Sustainable Food Agricultural Land and the Land Acquisition for Development for the Public Interest, as amended by the Job Creation Law, stipulates development in the public interest for the prosperity and improvement of the people's economy. Sustainability solutions seeking sustainable models for industrial growth without compromising public welfare.